2022
DOI: 10.1136/bmjopen-2021-059934
|View full text |Cite
|
Sign up to set email alerts
|

Time to detection of anaemia and its predictors among women of reproductive-age living with HIV/AIDS initiating ART at public hospitals, Southwest Ethiopia: a multicentre retrospective follow-up study

Abstract: ObjectiveTo assess the time to development of anaemia and its predictors among women of reproductive-age receiving antiretroviral therapy (ART) in public hospitals, Southwest Ethiopia.DesignHospital-based retrospective follow-up studySettingMizan-Tepi University Teaching Hospital, and Gebretsadik Shawo General Hospital Southwest Ethiopia.ParticipantsA total of 389 records of women living with HIV/AIDS at public hospitals were reviewed using a systematic sampling method. The data were entered using Epi-Data Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
(54 reference statements)
1
2
0
Order By: Relevance
“…44 In another study in Ethiopia, women with baseline opportunistic infections and women who were on ART for a long duration were significantly associated with anemia among women living with HIV/AIDS. 45 The above findings are comparable to a study by 46 who reported that factors that often contributed to the risk of developing anemia in HIV infection include the presence of opportunistic infections, sex, and a low CD4+ T-lymphocyte count. 47 This current study reported unsuppressed viral load and CD4-count less than 200 cells/mm 3 had a significant association with anemia.…”
supporting
confidence: 86%
“…44 In another study in Ethiopia, women with baseline opportunistic infections and women who were on ART for a long duration were significantly associated with anemia among women living with HIV/AIDS. 45 The above findings are comparable to a study by 46 who reported that factors that often contributed to the risk of developing anemia in HIV infection include the presence of opportunistic infections, sex, and a low CD4+ T-lymphocyte count. 47 This current study reported unsuppressed viral load and CD4-count less than 200 cells/mm 3 had a significant association with anemia.…”
supporting
confidence: 86%
“…A study by Belay et al revealed a high prevalence of anemia, reaching 54.9% among the participants [ 39 ]. The incidence rate of anemia was reported at 12.07 per 100 people/month, emphasizing the substantial risk associated with ART.…”
Section: Burden Of Anemia In People With Hivmentioning
confidence: 99%
“…The incidence rate of anemia was reported at 12.07 per 100 people/month, emphasizing the substantial risk associated with ART. Interestingly, the study suggests a temporal aspect, with 2.97% of women developing anemia in the first 6 months, escalating to 80.26% in the last 6 months of follow-up [ 39 ]. This temporal trend raises questions about the prolonged use of ART and its potential contribution to anemia development.…”
Section: Burden Of Anemia In People With Hivmentioning
confidence: 99%